2002
DOI: 10.1002/1521-396x(200204)190:3<631::aid-pssa631>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Level Repulsion of Localised Excitons Observed in Near-Field Photoluminescence Spectra

Abstract: Subject classification: 73.21.Hb; 78.55.Cr; 81.05.Ea; S7.12 GaAs/GaAlAs quantum wires grown by modulated flow rate metalorganic chemical vapour deposition were investigated by spatially resolved photoluminescence spectroscopy using a scanning near-field optical microscope. It was found that the wires decompose into a series of regions that emit luminescence of varying intensity. The spectra of these regions feature several narrow emission lines, which means that there is a series of more or less localised e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…It was concluded that the 3-meV peak in the autocorrelation is not related to level repulsion predicted for a statistical disorder potential with a single correlation length. Recently, autocorrelation spectra from disordered quantum wires 5 have been interpreted as being consistent with the predicted level repulsion scenario.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…It was concluded that the 3-meV peak in the autocorrelation is not related to level repulsion predicted for a statistical disorder potential with a single correlation length. Recently, autocorrelation spectra from disordered quantum wires 5 have been interpreted as being consistent with the predicted level repulsion scenario.…”
Section: Introductionmentioning
confidence: 67%
“…Recently, there has been considerable experimental [1][2][3][4][5][6][7] and theoretical interest 8,9 in studying the effects of excitonic level repulsion in disordered semiconductor nanostructures, e.g., narrow quantum wells and wires. In such systems, interface roughness and alloy fluctuations on a nanometer scale lead to spatial variations in the effective excitonic center-of-mass potential that tend to localize the excitonic wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…We applied the same analysis to our data as that described elsewhere. 11,12,14 The probability to find two exciton emission lines separated energetically by ⌬E is related to the average of the self-convolution of the normalized near-field PL spectra S i (E),…”
Section: B Level Repulsionmentioning
confidence: 99%
“…[11][12][13][14] In all these papers the interpretation of the experimental results is based on numerical solutions of the exciton center-of-mass ͑c.m.͒ Schrödinger equation in a disordered potential with a given correlation length and average potential amplitude. 7,11 The computed exciton eigenstates and energies are used to simulate near-field absorption spectra and their statistical analysis to fit the experiment, tuning the parameters of the potential.…”
Section: Introductionmentioning
confidence: 99%
“…We consider this very strong evidence for quantum mechanical level repulsion in disordered semiconductor nanostructures. Similar conclusions are drawn in a recent investigation of autocorrelation spectra of V-groove QWR [27]. Energ (meV) Fig.…”
Section: Energy (Ev)mentioning
confidence: 99%